JACIII Distinguished Editor & Outstanding Reviewer Awards 2025 (Journal of advanced computational intelligence and intelligent informatics, 2025)
The JACIII Distinguished Editor and Outstanding Reviewer Awards were established for the purpose to honor editors who have made a significant contribution to the growth of the JACIII in 2018 and to acknowledge reviewers who have made a significant contribution to reviewing in 2024. We express our deepest gratitude for their professional work, which we believe conductive to development of not only the JACIII but also scientific research.